Albumén: generador productivo para la agricultura regional - plan parcial alveolo suburbano Calle 80 (2019)
Sabana Occidente currently presents an exchange of organic products with Sabana Centro and a source of food for the city of Bogotá, the demand presented by these two regions on Sabana Occidente positions Sabana Occidente in an important place for the production of food, food that generate waste for different reasons, such as poor handling in the harvest, fertilizer materials of poor quality and poor employment also generates loss, the loss of food causes different impacts not only environmental, but also socioeconomic. Statement that evidences the need for management control in food handling before reaching a stage of commercialization where the concept of loss is transformed by the concept of food waste, in these previous stages it is necessary that food and its non-genetic manipulation has control, in good manufacturing practices and in the search for tools that promote the use of agricultural land, taking care of the environment and the commercial benefit of the region, through a project with a regional impact that controls and provide research inputs to producers.